Philosophical Ontology, Axiology, and Epistemology Approaches in Developing Literacy through Differentiated Instruction Strategies in Elementary Schools - Anggraini, Dhea Ayu; Suciptaningsih, Oktaviani Adhi; Anggraini , Ade Eka; Kuswandi , Dedi; Ramli, M. (Eduvest - Journal of Universal Studies, 2025)
In the contemporary educational landscape, integrating philosophical frameworks—ontology, axiology, and epistemology—into differentiated instruction strategies is essential for enhancing literacy in elementary schools. This study employs a literature review methodology, analyzing 14 reviewed articles to explore how these philosophical approaches inform effective teaching practices. The findings reveal that educators' perceptions of knowledge (ontology) significantly influence literacy strategies, while understanding values (axiology) is crucial for creating inclusive learning environments. Additionally, students' epistemological beliefs impact their engagement with literacy instruction, highlighting the need for educators to address these beliefs in their teaching. The implications of this research suggest that a comprehensive framework incorporating these philosophical dimensions can improve literacy outcomes and foster equitable learning opportunities for diverse learners.